1981
DOI: 10.1037/0021-9010.66.4.422
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics of adult women with low and high profiles on the SCII or SVIB occupational scales.

Abstract: Investigated how women (aged 25 yrs and over) with low profiles (LP) on the Strong-Campbell Interest Inventory (SCII) or SVIB female Occupational Scales differ from women who have high profiles (HP) with respect to measured personality characteristics (California Psychological Inventory [CPI]) and vocational needs (Minnesota Importance Questionnaire [MIQ]). 467 Ss for both SCII and SVIB groups, LP Ss differed from HP Ss on 35 CPI items and scored significantly lower on 9 CPI scales (e.g., Dominance, Capacity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…These revisions are appealing and plausible ideas for coping with person-work interactions and their outcomes that everyone has difficulty predicting. This group also continues to examine and revise the instrumentation (Shubsachs et al 1978), the related occupational classifica tion , and the hypotheses in the theory (Stickney 1978, Murray 1979, Sloan 1979.…”
Section: Theorymentioning
confidence: 98%
“…These revisions are appealing and plausible ideas for coping with person-work interactions and their outcomes that everyone has difficulty predicting. This group also continues to examine and revise the instrumentation (Shubsachs et al 1978), the related occupational classifica tion , and the hypotheses in the theory (Stickney 1978, Murray 1979, Sloan 1979.…”
Section: Theorymentioning
confidence: 98%
“…One such topic is to establish the links, if any, between CPI folk scales and the three-vector model and major instruments in occupational assessment, in particular Holland's Self-Directed Search and his hexagonal model and the Strong Interest Inventory (Campbell & Hansen, 1981). A good start has been made along this road (see Doran, 1979;Johnson, Flammer, & Nelson, 1975;Murray, 1980) in regard to the scales of the CPI, but no findings have, as yet, been reported for the three-vector model.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was found that women with high profiles on both the SVIB and the sen preferred writing, public speaking, law, politics, or managerial career items significantly more than women with low profiles (Murray, 1981 ). Additionally, low profile women did not have high preferences for SVIB and sen academic orientation scales and career extroversion dimensions (Murray, 1981).…”
Section: Early Studies Using the Svib And The Cpimentioning
confidence: 92%
“…According to Johnson, Nelson, & Flammer (1975), "social" CPI dimensions like Self-acceptance, Socialization, These studies on the precursors of today's sn (the SVIB) and CPI gave insight into the meaning of the scales themselves and how the measures could have been used to portray group differences. However, more recent work with newer versions provided information between groups in terms of differences and similarities in membership (Murray, 1981) and…”
Section: Early Studies Using the Svib And The Cpimentioning
confidence: 99%
See 1 more Smart Citation